The trade wars of the USA, China, and the EU the global economy in the age of populism - Günar, Altuğ, 1985- (Lexington Books, 2021)
"The book is investigating the developments after the 2008 crisis. The incompatible tone among the populist leaders with a liberal trade system led nations to disintegrate in the fields of economy and to protect their countries under the shadow of populism which is caused trade wars between world-leading economies"--